he Cosmopolitan Virus: Lessons from COVID-19 for Reconfiguring the Nation-State and Global Governance - Millán, Natalia; Santander, Guillermo (Geopolítica(s). Revista de estudios sobre espacio y poder, 2020)
The social, economic, and political crisis that has developed due to the COVID-19 pandemic is affecting all areas of human organizations. This epidemic has exposed the multidimensional vulnerability of contemporary societies configured under the logic of global capitalism. Within this framework, the article analyses, with a cosmopolitan approach, the impact of the pandemic from the local/global dialectic as well as the possible response scenarios to this transnational crisis. The article concludes that there is a need to reconfigure and strengthen nation states, not only to offer protection and public services to their citizens, but also to develop a cosmopolitan perspective to understand and manage the transnational threats thathumanity faces.
Keywords: COVID-19 pandemic; cosmopolitanism; human vulnerability; capitalism; global risks